Unraveling the effects of Lactobacillus sakei inoculation on the microbial quality and bacterial community diversity of chili sauce by high-throughput sequencing - ZHANG,Yalin (2022)
Abstract In this study, the effects of the starter culture Lactobacillus sakei on microbial quality and the bacterial community diversity of chili sauce were investigated. In starter culture inoculated chili sauce (CPN sample), Lactobacillus spp. was predominant bacteria with 86.08% of the relative abundance on the 30th day of fermentation. Meanwhile, the spoilage organisms and pathogenic bacteria, including Staphylococcus spp., Enterobacter spp., Pseudomonas spp. and Neorhizobium spp. were nearly undetectable in starter culture inoculated chili sauce. In contrast, Lactobacillus spp. and Weissella spp. were predominant bacteria, and trace Pseudomonas spp. and Neorhizobium spp. were still detectable at the end of fermentation in the spontaneous fermentation (CPS sample). These results revealed that L. sakei could be used as a potential starter culture for the microbial quality improvement.